2007
DOI: 10.1128/jb.01375-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IspC, an 86-Kilodalton Protein Target of Humoral Immune Response to Infection with Listeria monocytogenes Serotype 4b, as a Novel Surface Autolysin

Abstract: We identified and biochemically characterized a novel surface-localized autolysin from Listeria monocytogenes serotype 4b, an 86-kDa protein consisting of 774 amino acids and known from our previous studies as the target (designated IspC) of the humoral immune response to listerial infection. Recombinant IspC, expressed in Escherichia coli, was purified and used to raise specific rabbit polyclonal antibodies for protein characterization. The native IspC was detected in all growth phases at a relatively stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…8A). This finding correlated well with the result of a previous study which showed by reverse transcription-PCR (RT-PCR) that the IspC gene was transcribed at the highest levels during early log phase (27). The IspC protein was detectable in all growth conditions examined in this study; however, particularly low levels of expression were observed during growth in BHI broth supplemented with 10% (vol/wt) NaCl (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…8A). This finding correlated well with the result of a previous study which showed by reverse transcription-PCR (RT-PCR) that the IspC gene was transcribed at the highest levels during early log phase (27). The IspC protein was detectable in all growth conditions examined in this study; however, particularly low levels of expression were observed during growth in BHI broth supplemented with 10% (vol/wt) NaCl (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…However, despite weak activity of the ispC promoter, cells grown in UVM were still detectable by immunofluorescence microscopy with an anti-IspC MAb. This is likely because IspC is a very stable protein (Ronholm et al, unpublished) (27), and even minor expression during any growth phase leads to surface protein accumulation. The anti-IspC MAb was also able to detect cells grown in Fraser broth almost as well as cells grown in BHI broth.…”
Section: Discussionmentioning
confidence: 99%
“…Although L. monocytogenes encodes a number of peptidoglycan hydrolases (including p45, p60, lmo0327, Auto, Ami, and IspC) (48,49,67), none of these enzymes appears to be capable of compensating for the loss of NamA. This lends support to the hypothesis that hydrolases fulfill distinctly important and specific functions in cell wall physiology, although some of these functions are likely to be complementary.…”
Section: Discussionmentioning
confidence: 52%
“…Seven peptidoglycan hydrolases in L. monocytogenes have been identified and at least partially characterized. These hydrolases are p60 (also known as CwhA or Iap) (16,25,26,31,47,71), p45 (53), Ami (38,39), Auto (5, 7), NamA (also known as MurA) (10,33,36), lmo0327 (49), and IspC (67)(68)(69). While most of these proteins contain recognizable domains linked to murein hydrolase activity and cell wall binding and/or associations (7), many display unique characteristics associated with the regulation of catalytic activity (5) or with the anchoring of the proteins to the cell wall (68) as well as distinct activities relating to cell wall structure and function.…”
mentioning
confidence: 99%
“…Polyclonal antibody (PAb) production was performed as previously described (31). Briefly, female New Zealand White rabbits (Charles River Laboratories, Senneville, Quebec, Canada) age 2 to 3 months were immunized with recombinant proteins purified by metal affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%